2017
DOI: 10.4236/ijcm.2017.812063
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cognitive Aspects and Dysphagia in Patients with Amyotrophic Lateral Sclerosis: Preliminary Report

Abstract: Introduction: Cognitive impairment has been identified in 30% -50% of the population with Amyotrophic Lateral Sclerosis (ALS). Among these patients, dysphagia is not only a very common symptom but also one of the main bulbar symptoms. Objective: To correlate cognitive function and dysphagia in patients with ALS. Methods: a cross-sectional study. Criteria for inclusion were an ALS diagnosis and the signing of the consent form. Criteria for exclusion were patients who had undergone speech therapy, patients withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Cognitive impairment, as one of the non-motor symptoms, is a common complication in PD and also attention and frontal-executive functions compared to other cognitive domains are more involved in PD (14,26). Impairments affected some aspects of cognitive function are caused due to brain damages, which affect the oral phase of swallowing (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive impairment, as one of the non-motor symptoms, is a common complication in PD and also attention and frontal-executive functions compared to other cognitive domains are more involved in PD (14,26). Impairments affected some aspects of cognitive function are caused due to brain damages, which affect the oral phase of swallowing (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that there is a relationship between dysphagia and cognitive impairment (14)(15)(16)(17)(18). For examples, Yang Jo et al (17), in a study indicated that visual attention and executive function impairment may affect oral phase of swallowing in stroke patients.…”
Section: Introductionmentioning
confidence: 99%